Nutrient and toxic element concentrations in the endemic anchusa leptophylla roemer & schultes subsp. tomentosa (BOISS.) CHAMB - Turkoglu, Ismail; Turkoglu, Semra; Parlak, Akif Evren (Parlar Scientific Publications, 2019)
For centuries, people have used heavy metals for various purposes such as accessories, weapons, water pipes etc. without knowing their effects. In industrial zones with the initiation of burning coals that include heavy metals following industrializa-tion and in the world and our country where we are exposed to ever-increasing traffic congestion, the heavy metal portions have reached extreme magni-tudes with the increase in the amounts of heavy metals in the environment as well as many other pollutants. These matters do not only accumulate in organisms, but also could remain in dangerous densities in ecosystems by traveling around food chains. In this study, heavy metals and their con-centrations in plants were investigated. In the present study, the macronutrient, micro-nutrient and toxic metal compositions in the leaves and flowers of A. leptophylla were determined by the Inductively Coupled Plasma Optical Emission Spectrophotometer ICP-OES), and the mineral concentrations of the plant were evaluated. The information on the five macronutrient (Ca, Mg, P, Si, Na), the eight micronutrient (Cu, Fe, Mn, Co, Se, Zn, B, Ba) and the six toxic element (As, Al, Cd, Cr, Pb, Ni) concentrations were separately combined. According to the obtained results, even though several minerals were determined to be in proper limits, toxic minerals, such as As, Al, Ni, Cr and Pb, were determined to high limits. As a result, when the heavy metal compositions of the Anchusa plant are examined, it has been shown that the plant can be used as a bioacumula-tor. © 2019 Parlar Scientific Publications. All rights reserved.
Keywords: Anchusa leptophylla; Macronutricnt; Micronutricnt; Toxic element